Thermostability enhancement of the α-carbonic anhydrase from Sulfurihydrogenibium yellowstonense by using the anchoring-and-self-labelling-protein-tag system (ASLtag) - Sonia Del Prete; Rosa Merlo; Anna Valenti; Rosanna Mattossovich; Mosè Rossi; Vincenzo Carginale; Claudiu T. Supuran; Giuseppe Perugino; Clemente Capasso (Taylor & Francis Group, 2019)
Carbonic anhydrases (CAs, EC 4.2.1.1) are a superfamily of ubiquitous metalloenzymes present in all living organisms on the planet. They are classified into seven genetically distinct families and catalyse the hydration reaction of carbon dioxide to bicarbonate and protons, as well as the opposite reaction. CAs were proposed to be used for biotechnological applications, such as the post-combustion carbon capture processes. In this context, there is a great interest in searching CAs with robust chemical and physical properties. Here, we describe the enhancement of thermostability of the α-CA from Sulfurihydrogenibium yellowstonense (SspCA) by using the anchoring-and-self-labelling-protein-tag system (ASLtag). The anchored chimeric H5-SspCA was active for the CO2 hydration reaction and its thermostability increased when the cells were heated for a prolonged period at high temperatures (e.g. 70 °C). The ASLtag can be considered as a useful method for enhancing the thermostability of a protein useful for biotechnological applications, which often need harsh operating conditions.